The Influence of Environmental, Social, and Governance (ESG), Political Connections, Gender Diversity, and Capital Intensity on Tax Avoidance - Novia Indri Pratiwi; Luk Luk Fuadah; Yunisvita Yunisvita (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This study aims to examine the influence of Environmental, Social, and Governance (ESG), Political Connections, Gender Diversity, and Capital Intensity on Tax Avoidance. The research object used in this study is companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The purposive sampling method was used to select samples that met the criteria of this study and obtained as many as 27 companies that met the criteria. The research period is from 2018 to 2022, so that the total data observations amounted to 135 observations. The secondary data used in this study was obtained from the Annual Report & Sustainability Report. The results of the study show that Environmental, Social, and Governance (ESG) has no effect on tax avoidance, while political connections, gender diversity, and capital intensity have a positive effect on tax avoidance.